System train paths as key to efficient infrastructure usage for on-track competition in ITF-regimes. (December 2019) - Smoliner, Martin
Abstract: The liberalization of railway markets considerably affects timetabling and long-term infrastructure development. This is especially relevant for countries aligned to the "integrated periodic timetable" (known as ITF, short for German "Integrierter Taktfahrplan"), which requires cost-intensive infrastructure measures. Since both timetable and infrastructure must be developed jointly, it is not financially sustainable to design infrastructure upon demand for short-term open access services only. In general, legislation supports ITF. Slot allocation processes, however, potentially result in the worsening of overall network performance in some countries due to vague implementation rules. Firstly, the costs of the ITF planning philosophy on long-term infrastructure development are analysed based on the example of the Austrian railway network. Relevant investments are added up to compute the percentage of ITF-relevant infrastructure measures. Secondly, the characteristics of system train paths are identified to establish a schedule of pre-defined train paths that guarantee the full ITF functionality. The scheme of a system train path derived from this work is to be used for slot allocation processes implemented hand in hand with public tendering in order to use the infrastructure as effectively as possible. This scheme allows the implementation of the ITF together with an open railway market, which will offer the best possible network-wide customer benefits and guarantee an economic use of the infrastructure. Graphical abstract: Image 1 Highlights: One third of railway infrastructure investments in Austria are related to the ITF. High investments request an optimal infrastructure utilization. An integrated periodic timetable (ITF) can by determined by system train paths. System train paths combine positive effects of competition and periodic timetables.